The Controversies of Accounting for Employee Stock Options: - Liu, Xiang; Han, Yongliang Stanley (Journal of Accounting, Business and Management (JABM), 2025)
In this paper, using a combined method of historical and theoretical analyses, we investigate the controversial accounting treatment of employee stock options (ESOs) by the financial accounting standard board (FASB) and the securities and exchange commission (SEC) in the U.S. We first review the standard setting history of ESOs and then discuss the pros and cons of expensing ESOs which is the current accounting practice. This helps understand why so much controversy existed on the current accounting treatment. Next, we propose four alternative classifications of SOEs and analyze each of them using the financial accounting standards board (FASB) conceptual framework. The arguable vague classification of ESOs in the current conceptual framework contributes to these controversies. Finally, we raise several empirical testing questions whose answers may help guide for future standard setting of ESOs. This paper contributes to the literature of accounting standard setting by critiquing the current practice. We believe it is beneficial to keep other solutions open for future discussion